أثر الفكر النحوي الكوفي في كتب تيسير النحو كتاب في انحو العربي نقد و توجيه للمخزومي أنموذجا - علاق, لخويمس, الصديق حمزة; تواتي, محمد (Univercty of Eloued, 2020)
- ولقد توصلنا من خلال بحثنا هذا إلى مجموعة من النتائج نذكر أهمها في النقاط التالية: - 1- يعتبر كتاب المخزومي "في النّحو العربي نقد وتوجيه" من أهمّ الكتب النّحوية في الدّراسات اللّغوية الحديثة، وذلك لما يزخر به من آراء تيسيرية مبسّطة، كما أنّ صاحبه انتهج فيه طريق الاعتدال في الأخذ بالآراء رغم ميله للمذهب الكوفي، والّذي يبدو جليا من خلال آرائه الّتي عرضها فيه. - 2- التّيسير النّحوي قديم قدم النّحو ذاته، فالنّحاة الأوائل تنبهوا إلى ضرورة تقريب وتسهيل النّحو للنّاشئة المتعلّمين. - 3- يعدّ المخزومي من أهمّ روّاد التّيسير في العصر الحديث، وذلك من خلال مؤلّفاته النّحوية. - 4- لقد أفاد المخزومي من المدارس النّحوية سواء البصرية أو الكوفية وغيرهما، حتّى أنّه أبقى على بعض المصطلحات الّتي جاء بها الخليل ممّا يدلّ على دراسته الموضوعيّة، غير أنّه وجد ضالّته في المدرسة الكوفية لأنّها ذات طابع تيسيري، وهو ما يسعى إليه المخزومي وغيره من روّاد التّيسير. - 5- تيسير النّحو عند مهدي المخزومي لم يكن اختصارًا لموضوعاته ولا حذفًا ولا اختزالًا وإنًما كان تجديدًا لما يلائم القدرات المعرفية للمتعلّمين، كي يسهل فهم النحو واستيعاب موضوعاته. - 6- الشّكوى من تعلّم النّحو وصعوبته على الدّارسين كانت أهم الأسباب الّتي دفعت بالمخزومي لانتهاج طريق التّيسير. - 7- حاول مهدي المخزومي من خلال آرائه التّيسيرية أن يعطي انطباعًا مهمًّا بعدم صعوبة النّحو العربي فهو ليّن قابل لمواكبة العصر. - 8- يبدو جليًّا تأثّر المخزومي بالمنهج الخليلي إضافة إلى تأثره بآراء أستاذه إبراهيم مصطفى خاصّة في موضوع الإعراب. - 9- جعل مهدي المخزومي الجملة موضوعًا للدّرس النّحوي، وما يطرأ عليها من المعاني في مقامات الكلام، كما أنكر على النّحاة اقتصارهم في مفهوم الإعراب على أواخر الكلمات فقط. - 10- كان مهدي المخزومي شديد الرّفض لنظريّة العامل النّحوي، كما جعل من أسس تيسير النّحو إلغاء القول بها لأنّها نتيجة تأثّر النّحو العربي بالفلسفة والمنطق اليوناني. - 11- تأثّر المخزومي بالنّحو الكوفي في الأصول والفروع ، حيث انتصر للمذهب الكوفي في اختباراته النحوية، حينما ذهب معهم إلى القول بالفعل الدائم واعتبار أسماء الأفعال أفعالًا خلافًا للبصريين، كما ذهب إلى جواز تقديم الفاعل أو نائبه عن فعلهما، وغيرهما من الآراء الّتي وافق الكوفيين فيها . - 12- أعاد المخزومي تبويب موضوعات النّحو على أساس المعنى لا على أساس العمل الإعرابي، كما درس الأدوات حسب المعاني الّتي تؤدّيها داخل السّياق. وختام الكلام نأمل أن يكون هذا البحث قد عرض صورة واضحة لمعالم الدّرس النحوي عند مهدي المخزومي في كتابه "في النحو العربي نقد وتوجيه"، مع تمنياتنا أن تكون هذه الدّراسة نافعة بمادّتها ولو بالشّيء القليل لطلبة العلم، ومحبّي اللّغة العربيّة في كلّ أرجاء المعمورة. Through our research, we have reached a set of results, the most important of which are in the following points: 1- Al-Makhzoumi’s book “In Arabic Grammar, Criticism and Guidance” is considered one of the most important grammatical books in modern linguistic studies, due to its abundant facilitative opinions, and its author followed the path of moderation in taking opinions despite his inclination to the Kufic doctrine, which is evident through His opinions that he presented it. 2- Syntactic facilitation is as old as the grammar itself. Early sculptors noted the necessity of bringing closer and facilitating grammar to the educated young. 3- Al-Makhzoumi is considered one of the most important pioneers of facilitation in the modern era, through his grammatical writings. 4- Al-Makhzoumi has benefited from grammatical schools, whether al-visual, kufic, and others, so that he kept some of the terms that Hebron came up with, which indicates his objective study, but he found his way in the kufic school because it has a facilitative character, which is what Makhzoumi and other pioneers seek Facilitation. 5- Facilitating grammar, according to Mahdi Al-Makhzoumi, was not an abbreviation of its topics, an omission or a shorthand, but rather a renewal of what suits the cognitive abilities of learners, in order to facilitate understanding of grammar and the comprehension of its topics. 6- Complaints about learning grammar and its difficulty for learners were the most important reasons that pushed Makhzoumi to pursue the path of facilitation. 7- Mahdi Makhzoumi, through his facilitative views, tried to give an important impression that Arabic grammar is not difficult, as it is soft and able to keep pace with the times. 8- It seems clear that Makhzoumi was influenced by the Khalili approach, in addition to his influence on the views of his teacher, Ibrahim Mustafa, in particular on the subject of parsing. 9- Mahdi Makhzoumi made the sentence a subject for a grammatical lesson, and the meanings that occur to it in terms of speech, and he denied to the grammarians that they limit the concept of parsing to only the last words. 10- Mahdi Al-Makhzoumi was a strong rejection of the theory of the grammatical factor, and he made one of the foundations of facilitating grammar to cancel saying it because it was a result of the influence of Arabic grammar with Greek philosophy and logic. 11- Al-Makhzoumi was influenced by the Kufic grammar in its origins and branches, where he triumphed for the Kufic doctrine in its grammatical tests, when he went with them to say the permanent verb and to consider the names of verbs as actions contrary to the visionaries, and also went to the permissibility of introducing the subject or his deputy about their action, and other opinions in which the Kufists agreed . 12- Al-Makhzoumi re-classified grammatical topics on the basis of meaning rather than on the basis of syntactic work, and he also studied the tools according to the meanings that they perform within the context. Concluding the speech, we hope that this research has presented a clear picture of the features of the grammatical lesson of Mahdi Al-Makhzoumi in his book “In Arabic Grammar Criticism and Guidance”, with our wishes that this study will be useful in its material, even if a little, for students of knowledge, and lovers of the Arabic language all over the world.
Keywords: الفكر النّحوي- الكوفة - تيسير النّحو - المخزومي; Grammatical thought - Kufa - Facilitation of grammar - Makhzoumi